New Onset Depression and Anxiety After Spinal Fusion Surgery: Incidence and Risk Factors. Issue 16 (15th August 2020) - Bekeris, Janis; Wilson, Lauren A.; Fiasconaro, Megan; Poeran, Jashvant; Liu, Jiabin; Girardi, Federico; Memtsoudis, Stavros G.
Abstract : Study Design: Retrospective database study. Objective: We sought to investigate trends and risk factors for new-onset anxiety and/or depression within 6 months after elective spine surgery. Summary of Background Data: Surgery represents a stressful experience associated with a number of physiological and psychological consequences. A subset of patients develop clinically significant symptoms of new-onset anxiety or depression. However, the incidence of and risk factors for these adverse outcomes after spine surgery remain ill-defined. Methods: We performed a retrospective analysis including anterior cervical discectomy and fusion and posterior lumbar fusion cases from 2012 to 2015, utilizing the Truven MarketScan database. Primary outcomes were new-onset depression, new-onset anxiety, and new-onset depression and/or anxiety after surgery. Potential risk factors included patient demographics, comorbidities, hospital and procedural characteristics as well as perioperative opioid regimens. Multivariable logistic regression models measured associations between risk factors and outcomes. Odds ratios (OR) were reported and results with P < 0.0167 were considered statistically significant. Results: Among 39, 495 unique patients, overall incidence of new-onset depression and anxiety was 6% and 11.2%, respectively. In adjusted analyses, significant risk factors across all three outcomes included chronic opioid use (ORs ranging from 1.31 to 2.93; P < 0.01), female sex (ORs ranging from 1.25 to 1.67; P < 0.01), longer length of stay (ORs ranging from 1.05 to 1.08; P < 0.01), and readmission within 6 months of surgery (OR ranging from 1.31 to 1.68; P < 0.01). Conclusion: We identified several risk factors contributing to increased odds of new-onset depression and/or anxiety after spine fusion surgery. These data may aid the implementation of preventative measures among identified high-risk patients. Level of Evidence: 3 Abstract : Supplemental Digital Content is available in the textIn this retrospective study, we evaluated incidence of and risk factors for new-onset depression and anxiety within 6 months of spine surgery. Incidence of new-onset depression and anxiety was 6% and 11%, respectively. Risk factors included younger age, female sex, and chronic opioid use.